Elderly people with dementia: factors related to informal caregivers’ quality of life and burden (Research, Society and Development, 2023)
Objective: To associate variables related to caregivers’ activity with their QoL and burden and to correlate QoL with burden particularly regarding informal caregivers of elderly people with dementia. Materials: data collected from online and cross-sectional survey with 112 family (i.e. informal) caregivers of elderly people with dementia, from November 2021 to July 2022 through: (i) sociodemographic-clinical questionnaire, (ii) Informal Caregiver Burden Assessment Questionnaire, and (iii) Quality of Life Questionnaire - Control, Autonomy, Self-realization and Pleasure (CASP-19). Method: Descriptive analysis, Spearman correlation and Bonferroni post-hoc were performed. Results: For QoL, a negative correlation of moderate level was noted for burden (ρspearman = – 0.656; p < 0.01). Caregivers who performed paid work (36.3 ± 3.03) and who felt valued (38.8 ± 3.12) had a higher QoL score. Those who did not perform paid work (90.3 ± 5.82) and who did not feel valued (77.3 ± 5.39) showed greater burden. Conclusion: The higher the burden score, the lower the QoL score. Performing paid work and feeling valued correlated to higher QoL score while not engaging in paid work and not feeling valued were associated with greater burden.